Derivada de uma função num ponto: uma forma significativa de introduzir o conceito - D'Avoglio, Armando Raphael (2002)
This is na intervention research. It was carried through with students who initiated the superior course, in the area of Accurate. The objective of it is to investigate if the introduction of the concept of derivative of a function in a point, by means of familiar concepts to the students and with a certain relationship with the daily one of them, as of speed for example, it would produce effect for the improvement of the learning of this notion. The intervention was carried through by the application of a didactic sequence, contends seven activities. In the elaboration of the same one, basic concepts of kinematics had been used, in order to contribute with that the student participated of the systematization of the concept of derivative of a function in a point. And, with estimated of that, if thus it occurred, they could give more meant to the new concept, becoming its more significant learning. For the analyses of the results, in we support them in the Theory of the Significant Learning of AUSUBEL. Our conclusion is that it had advantages in this form to introduce derived; that the student can give more meant to the this notion; e that had improvements in the understanding of the same one